Current Status of Energy Production from Solid Biomass in Southern Italy - Cristina Moliner; Elisabetta Arato; Filippo Marchelli (Energies, 2021)
This work analyses and discusses data on thermochemical plants in Southern Italy that are fed with solid biomass. The analysis takes into account the biomass availability and potential together with the cost-benefit analysis using technology development and economic indicators (LCOE). A total of 63,762 units have been categorised according to the employed technology and produced energy: power plants for electricity production or cogeneration plants for combined heat and electricity production (53 plants) and thermal units for heat production (63,709 units). The eight regions of the area have noteworthy differences. In terms of electricity generated from solid biomass Calabria is by far the largest producer, followed by Apulia. Sicily, Sardinia and Molise provide lower amounts while Abruzzo, Basilicata and Campania generate almost negligible amounts. Regarding thermal production, Campania and Calabria are the largest producers, but Basilicata, Molise and Abruzzo generate the highest amount per capita. The area is far from fully exploiting its biomass potential, and there are also no district heating grids. Bioenergy can be remarkably competitive, provided that capital costs are relatively low and low-cost biomass is available, as it is the case of Italy. New applications and markets for sub-products (i.e., char, ash) would help in lowering the still not competitive economic indicators (LCOE).